Survey and new insights in the application of PCR‐based molecular markers for identification of HMW‐GS at the Glu‐B1 locus in durum and bread wheat. (4th July 2017) - Janni, Michela; Cadonici, Stefania; Pignone, Domenico; Marmiroli, Nelson
Abstract: Wheat, among all cereal grains, possesses unique characteristics conferred by gluten; in particular, high molecular weight glutenin subunits (HMW‐GS) are of considerable interest as they strictly relate to bread‐making quality and contribute to strengthening and stabilizing dough. Thus, the identification of allelic composition, in particular at the Glu‐B1 locus, is very important to wheat quality improvement. Several PCR‐based molecular markers to tag‐specific HMW glutenin genes encoding Bx and By subunits have been developed in recent years. This study provides a survey of the molecular markers developed for the HMW‐GS at the Glu‐B1 locus. In addition, a selection of molecular markers was tested on 31 durum and bread wheat cultivars containing the By8, By16, By9, Bx17, Bx6, Bx14 and Bx17 Glu‐B1 alleles, and a new assignation was defined for the ZSBy9_aF1/R3 molecular marker that was specific for the By20 allele. We believe the results constitute a practical guide for results that might be achieved by these molecular markers on populations and cultivars with high variability at the Glu‐B1 locus.